2015
DOI: 10.1021/acsami.5b07722
|View full text |Cite
|
Sign up to set email alerts
|

3D Micropatterned Surface Inspired by Salvinia molesta via Direct Laser Lithography

Abstract: Biomimetic functional surfaces are attracting increasing attention for their relevant technological applications. Despite these efforts, inherent limitations of microfabrication techniques prevent the replication of complex hierarchical microstructures. Using a 3D laser lithography technique, we fabricated a 3D patterned surface bioinspired to Salvinia molesta leaves. The artificial hairs, with crownlike heads, were reproduced by scaling down (ca. 100 times smaller) the dimensions of natural features, so that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 40 publications
2
138
0
1
Order By: Relevance
“…Persistent air layers under water (Salvinia effect) are discussed in [14,15,[53][54][55][56][57][58][59][60][61][62].…”
Section: Database Literature Methods and Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Persistent air layers under water (Salvinia effect) are discussed in [14,15,[53][54][55][56][57][58][59][60][61][62].…”
Section: Database Literature Methods and Materialsmentioning
confidence: 99%
“…Search machines like 'Google' provided (May 2016) some 600 000 hits for 'lotus effect' and some 520 000 hits for 'superhydrophobic'. [7], (b) from [62].…”
Section: (B) Crystallinitymentioning
confidence: 99%
See 1 more Smart Citation
“…The structures were written in an epoxy‐based resist, using DLW. Reproduced with permission . Copyright 2015, American Chemical Society.…”
Section: Fabrication Methods For 3d Structures With Overhanging Featumentioning
confidence: 99%
“…Bhushan proved that a structure can be created in the lab to mimic the behavior of salvinia; Sung's research indicated that the air-retaining properties can be greatly enhanced using the salvinia structure compared to the lotus one. Tricinci et al 22 used a 3D laser lithography technique to fabricate a 3D patterned surface bio-inspired by salvinia and the sample showed interesting properties of hydrophobicity and air retention when submerged under water. Holscher et al 23,24 fabricated a nanofur by a hot pulling method to mimic the salvinia effect cost-effectively.…”
mentioning
confidence: 99%